The Future of Smart Devices: Contextual Awareness - Ojo Bojaji (Ee Times Europe, 2019)
Silicon Root of Trust Goes Open Source, Boards and Solutions + ECE Insert: Radar and MEMS and VCSELs and PMICs, Special Report: Big Data.